Automatic Routing in Triage Process - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study investigates and characterizes the impact of different features of email on effective routing of email to domain experts. The findings of the study would help in understanding how machine learning techniques such as classification could be applied effectively to develop better automatic triage process in digital reference service. Cette étude examine et caractérise l'impact de différentes caractéristiques des courriels sur leur acheminement efficace aux experts du domaine. Les résultats de l'étude permettraient de comprendre comment les techniques d'apprentissages machine comme la classification pourraient être appliquées efficacement afin de développer de meilleurs processus de triage automatique pour les services de référence numérique.